2018
DOI: 10.1038/s41598-018-35045-8
|View full text |Cite
|
Sign up to set email alerts
|

Construction and characterization of a Saccharomyces cerevisiae strain able to grow on glucosamine as sole carbon and nitrogen source

Abstract: Saccharomyces cerevisiae can transport and phosphorylate glucosamine, but cannot grow on this amino sugar. While an enzyme catalyzing the reaction from glucosamine-6-phosphate to fructose-6-phosphate, necessary for glucosamine catabolism, is present in yeasts using N-acetylglucosamine as carbon source, a sequence homology search suggested that such an enzyme is absent from Saccharomyces cerevisiae. The gene YlNAG1 encoding glucosamine-6-phosphate deaminase from Yarrowia lipolytica was introduced into S. cerevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 69 publications
(77 reference statements)
1
2
0
Order By: Relevance
“…This reaction has been present in S. cerevisiae GEMs ever since the first S. cerevisiae GEM iFF708 from 2003 (Förster et al , 2003), and likewise in the here used Yeast8 model. However, the pan‐GEM‐derived model for this species indicated the absence of this reaction, which is consistent with absence of in vivo growth on N‐acetyl‐D‐glucosamine (Flores & Gancedo, 2018). Also, Yeast8 did not have genes associated with fifth step of CoA synthesis from (R)‐pantothenate, while our model construction pipeline annotated the gene YGR277C to this reaction, in consistence with the SGD database annotation (Cherry et al , 2012).…”
Section: Resultssupporting
confidence: 80%
“…This reaction has been present in S. cerevisiae GEMs ever since the first S. cerevisiae GEM iFF708 from 2003 (Förster et al , 2003), and likewise in the here used Yeast8 model. However, the pan‐GEM‐derived model for this species indicated the absence of this reaction, which is consistent with absence of in vivo growth on N‐acetyl‐D‐glucosamine (Flores & Gancedo, 2018). Also, Yeast8 did not have genes associated with fifth step of CoA synthesis from (R)‐pantothenate, while our model construction pipeline annotated the gene YGR277C to this reaction, in consistence with the SGD database annotation (Cherry et al , 2012).…”
Section: Resultssupporting
confidence: 80%
“…This enzymological approach led us to revisit GlcN utilization in Rhodococcus spp., using R. jostii and R. fascians as growing models, and to find new metabolic outputs when the microorganisms use GlcN as the sole carbon source (Cereijo et al, manuscript in preparation). Worthy of mentioning, the literature available concerning GlcN utilization by microorganisms is scarce and limited to a group ( Flores and Gancedo, 2018 ), including some Gram-positive bacteria ( Gaugué et al, 2013 ; Uhde et al, 2013 ; Álvarez-Añorve et al, 2016 ). Then, given that the allosteric properties of ADP-Glc PPases are linked to the major carbon assimilation pathways(s) in the organisms they belong to, their kinetic and regulatory characterization may help infer metabolic pathways occurring in the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, variable results regarding glucosamine have been observed in species such as Rhodotorula cycloclastica [23,24]. Furthermore, it has been found that some yeast species exhibit metabolic variability in their ability to utilize glucosamine as a carbon source [25]. Based on the morphological and biochemical characteristics, the yeast culture was identified as R. mucilaginosa.…”
Section: Resultsmentioning
confidence: 99%